1997
DOI: 10.1007/s002709900169
|View full text |Cite
|
Sign up to set email alerts
|

Massive Pulmonary Embolism: Treatment with Thrombus Fragmentation and Local Fibrinolysis with Recombinant Human-Tissue Plasminogen Activator

Abstract: Clot fragmentation and local fibrinolysis with rtPA was an effective therapy for massive pulmonary embolism. Bleeding at the puncture site was a frequent complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…Further studies are indicated to determine the most effective bolus dose, infusion rate and total dose of r-TPA that should be administered. Although higher doses of r-TPA were used in this study than in standard peripheral intravenous thrombolysis, and higher doses were used than in the study by Stock et al [30], no patient suffered haemorrhagic complications [7,12]. No patient had a contraindication to thrombolysis, but patient 4 had had a coronary artery bypass graft 17 days prior to thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Further studies are indicated to determine the most effective bolus dose, infusion rate and total dose of r-TPA that should be administered. Although higher doses of r-TPA were used in this study than in standard peripheral intravenous thrombolysis, and higher doses were used than in the study by Stock et al [30], no patient suffered haemorrhagic complications [7,12]. No patient had a contraindication to thrombolysis, but patient 4 had had a coronary artery bypass graft 17 days prior to thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Angiographic appearances improved, systemic blood pressure increased and right ventricular end diastolic and pulmonary artery pressures fell following mechanical clot fragmentation and administration of the bolus dose of streptokinase. Stock et al have recently reported five patients with massive PE in whom clot fragmentation was performed using a balloon catheter in addition to standard guidewires and angiographic catheters and in whom r-TPA was used as the local thrombolytic agent [30]. All patients were successfully treated with a significant decrease in pulmonary arterial pressure being recorded after treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Über den Einsatz einer Kombination von lokaler Katheterfragmentation in der frühen postoperativen Phase mit lokaler Lyse liegen nur anekdotische Berichte vor [1,10,25,26,35], ein Fall nach einem vergleichbar großen viszeralchirurgischen Oberbaucheingriff wird in der Literatur nicht beschrieben.…”
Section: Diskussionunclassified
“…Es stehen verschiedene Systeme zur perkutanen Embolektomie sowie zur Katheterfragmentation und -thrombektomie zur Verfügung [3,8,13,19,21,23,26,30,31,32,33,34,35].…”
Section: Diskussionunclassified
“…in Kombination mit einer kathetergestützten Thrombusfragmentation, eine sinnvolle und effektive Therapieoption darstellen kann[2,8,22,23,25,27]. Des Weiteren bleibt dem Patienten durch das interventionelle Verfahren ein operatives Vorgehen mit seiner eigenen postoperativen Morbidität und Letalität erspart[21].…”
unclassified